PH-Induced transformation of ligated Au25 to brighter Au23 nanoclusters. Issue 24 (1st May 2018) - Waszkielewicz, Magdalena; Olesiak-Banska, Joanna; Comby-Zerbino, Clothilde; Bertorelle, Franck; Dagany, Xavier; Bansal, Ashu K.; Sajjad, Muhammad T.; Samuel, Ifor D. W.; Sanader, Zeljka; Rozycka, Miroslawa; Wojtas, Magdalena; Matczyszyn, Katarzyna; et al.
Abstract : Size transformation and fluorescence enhancement of Au25 NCs at low pH. Abstract : Thiolate-protected gold nanoclusters have recently attracted considerable attention due to their size-dependent luminescence characterized by a long lifetime and large Stokes shift. However, the optimization of nanocluster properties such as the luminescence quantum yield is still a challenge. We report here the transformation of Au25 Capt18 (Capt labels captopril) nanoclusters occurring at low pH and yielding a product with a much increased luminescence quantum yield which we have identified as Au23 Capt17 . We applied a simple method of treatment with HCl to accomplish this transformation and we characterized the absorption and emission of the newly created ligated nanoclusters as well as their morphology. Based on DFT calculations we show which Au nanocluster size transformations can lead to highly luminescent species such as Au23 Capt17 .